2016
DOI: 10.3892/br.2016.650
|View full text |Cite
|
Sign up to set email alerts
|

Target and resistance-related proteins of recombinant mutant human tumor necrosis factor-related apoptosis-inducing ligand on myeloma cell lines

Abstract: Abstract. Recombinant mutant human tumor necrosis factor-related apoptosis-inducing ligand (rmhTRAIL) has become a potential therapeutic drug for multiple myeloma (MM). However, the exact targets and resistance mechanisms of rmhTRAIL on MM cells remain to be elucidated. The present study aimed to investigate the target and resistance-related proteins of rmhTRAIL on myeloma cell lines. A TRAIL-sensitive myeloma cell line, RPMI 8226, and a TRAIL-resistance one, U266, were chosen and the differentially expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…TRAIL has become a potential therapeutic drug for cancers, but effects are different between TRAIL-sensitive cancer cells and TRAIL-resistant cancer cells. TRAIL was sensitive to various types of cancer cells, including prostate and bladder cancer cells [ 20 ] and myeloma cell line RPMI 8226 [ 21 ], and significantly decreased cell proliferation rate in these cancer cells. Moreover, not all cancer cells are susceptible to TRAIL-mediated cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…TRAIL has become a potential therapeutic drug for cancers, but effects are different between TRAIL-sensitive cancer cells and TRAIL-resistant cancer cells. TRAIL was sensitive to various types of cancer cells, including prostate and bladder cancer cells [ 20 ] and myeloma cell line RPMI 8226 [ 21 ], and significantly decreased cell proliferation rate in these cancer cells. Moreover, not all cancer cells are susceptible to TRAIL-mediated cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis-Inducing Ligand (TRAIL) and agonistic Death Receptor antibodies have been completed in several tumour types [7][8][9] including MM [10]. Unfortunately, TRAIL resistance develops in vitro [11] and in clinical trials, TRAIL insensitivity may be present in most tumours [12]. Consequently combined therapy of TRAIL with other anti-tumour agents is required to restore the TRAIL sensitivity [9].…”
Section: Clinical Trials To Assess the Safety And Anti-cancer Activitmentioning
confidence: 99%
“…TRAIL can induce apoptosis of tumor cells without damaging normal cells. As the application of wild-type TRAIL has limited stability and biological activity, recombinant mutant human TRAIL (rmhTRAIL) has been developed [4]. It has been reported that rmhTRAIL can remarkably inhibit the proliferation of tumor cell lines from the lung, colon, and breast cancer [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that rmhTRAIL can remarkably inhibit the proliferation of tumor cell lines from the lung, colon, and breast cancer [5]. Because rmhTRAIL can selectively induce apoptosis in various types of tumor cells, including myeloma cells, it is a potential therapeutic drug for MM [4]. However, as some tumor cells from the breast, colon, and bone marrow are not sensitive to rmhTRAIL, the clinical application of rmhTRAIL is significantly limited [4,6].…”
Section: Introductionmentioning
confidence: 99%